(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the etiological and demographic pattern of poisoning among admitted patients in a tertiary care hospital of southern Punjab. Study Design: Retrospective Observational study Place and Duration of Study: This study was conducted at the department of Medicine (Medical unit 1), Bahawal Victoria Hospital (BVH), Bahawalpur from January, 2019 to December, 2019. Materials and Methods: All cases of acute poisoning admitted in Medical unit 1, through Accident & Emergency (A&D) department of BVH, Bahawalpur from January, 2019 to December, 2019 were included in the study. The etiological and demographic details were documented by using a specifically designed proforma in the light of their medical record files. Results: Out of 342 patients of acute poisoning enrolled in the study, 251 (73.4%) were females and 91 (26.6%) were males. The overall mean age was 23.58 years. Most cases of acute poisoning presented among 21- to 30-year of age group (44.4%) followed by 13- to 20-years of age group (41.8%). Majority of subjects were married (62%). The most common agent used for poisoning was paraphenylene diamine (PPD / Kala patthar) (49.4%) followed by organophosphorus (OP) compounds (40%). The reason of poisoning in majority of cases (96%) was suicidal attempt. Overall mortality among poisoning patients was 19.3%. PPD poisoning emerged the major contributor of mortality in 87.9% of cases. Conclusion: The majority of poisoning cases in our setup occurs in females of younger age group for suicidal attempt carrying substantial mortality. PPD (Kala Patthar) being the commonest and most lethal poison in such cases.